Optimizing MR imaging for detecting small tumors in the cerebellopontine angle and internal auditory canal. - Enzmann, D R; O'Donohue, J (American Journal of Neuroradiology, 1987)
Relative resolving power was used to determine the optimal MR imaging pulse sequence for detecting small tumors of the internal auditory canal and the cerebellopontine angle. Resolving power takes into consideration these important image characteristics: signal-to-noise ratio, contrast, and spatial resolution. The study was performed on a 1.5-T magnet using a 256 X 256 matrix and a 3-mm slice thickness. The TR ranged from 400-2000 msec; the number of excitations was either two or six; and the pixel size was 0.94, 0.78, or 0.63 mm. Theoretical calculations of relative resolving power were compared with the relative resolving power of 45 control patients and 15 patients with small tumors of the cerebellopontine angle or internal auditory canal. A TR of 800 msec was optimal from theoretical calculations and proved optimal in control and tumor patients. Scans obtained with TR = 2000 msec, TE = 80 msec were inferior to short TR scans; such scans could fail to detect intracanalicular tumors. The relative resolving power in patients exceeded theoretical calculations because of greater than expected image contrast caused by low CSF signal intensity secondary to CSF pulsation.